Problem prostytucji i handlu żywym towarem w Europie na przełomie XIX i XX wieku : przegląd literatury niemieckiej i austriackiej - Antonów, Radosław (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
In the nineteenth century the problem of prostitution and human trafficking was a serious security threat. Having recognized the scale of the phenomenon of prostitution and the breadth of criminal offenses accompanying it, national governments took appropriate measures, on both domestic and international arenas. Social initiatives were launched with the aim of exposing human trafficking. The abovementioned measures occurred alongside academic and journalistic analyses of the phenomena of prostitution and human trafficking. German and Austrian research were particularly valuable in this area
Keywords: prostytucja; handel żywym towarem; handel ludźmi; handel kobietami; kobiety; Europa